Activity of oxantel pamoate monotherapy and combination chemotherapy against Trichuris muris and hookworms: revival of an old drug. - Jennifer Keiser; Lucienne Tritten; Angelika Silbereisen; Benjamin Speich; Roberto Adelfio; Mireille Vargas (Public Library of Science (PLoS), 2013)
BACKGROUND: It is widely recognized that only a handful of drugs are available against soil-transmitted helminthiasis, all of which are characterized by a low efficacy against Trichuris trichiura, when administered as single doses. The re-evaluation of old, forgotten drugs is a promising strategy to identify alternative anthelminthic drug candidates or drug combinations. METHODOLOGY: We studied the activity of the veterinary drug oxantel pamoate against Trichuris muris, Ancylostoma ceylanicum and Necator americanus in vitro and in vivo. In addition, the dose-effect of oxantel pamoate combined with albendazole, mebendazole, levamisole, pyrantel pamoate and ivermectin was studied against T. muris in vitro and additive or synergistic combinations were followed up in vivo. PRINCIPAL FINDINGS: We calculated an ED50 of 4.7 mg/kg for oxantel pamoate against T. muris in mice. Combinations of oxantel pamoate with pyrantel pamoate behaved antagonistically in vitro (combination index (CI) = 2.53). Oxantel pamoate combined with levamisole, albendazole or ivermectin using ratios based on their ED50s revealed antagonistic effects in vivo (CI = 1.27, 1.90 and 1.27, respectively). A highly synergistic effect (CI = 0.15) was observed when oxantel pamoate-mebendazole was administered to T. muris-infected mice. Oxantel pamoate (10 mg/kg) lacked activity against Ancylostoma ceylanicum and Necator americanus in vivo. CONCLUSION/SIGNIFICANCE: Our study confirms the excellent trichuricidal properties of oxantel pamoate. Since the drug lacks activity against hookworms it is necessary to combine oxantel pamoate with a partner drug with anti-hookworm properties. Synergistic effects were observed for oxantel pamoate-mebendazole, hence this combination should be studied in more detail. Since, of the standard drugs, albendazole has the highest efficacy against hookworms, additional investigations on the combination effect of oxantel pamoate-albendazole should be launched.